(untitled) (Journal of the Spanish Institute for Strategic Studies, 2023)
The Earth could face the impact of a large object from the cosmos once again. This plausible, although unlikely, scenario exposes us as humanity to an unprecedented paradigm. The development of planetary defense strategies becomes essential, as does the need to define the regulatory framework for enabling its legal and political articulation while respecting human rights. This paper offers a prospective and transdisciplinary analysis based on a rigorous review of the current scientific-technical capabilities of asteroid mitigation. In turn, it examines the political-legal and bioethical implications of different scenarios derived from the cosmic impact threat. Through an extrapolation exercise, we propose the figure of the impact refugee and the deterritorialized state by adopting climate refugees and environmental risks as a reference. By considering geopolitical conflicts and the multiplicity of actors involved, the article concludes with the need to generate a prevention system that guarantees democratic procedures for decision-making in the face of catastrophic scenarios.